Patterns of Prescription of Private Practitioners in Bangladesh - Zahan, Tahmina; Bhuiyan, Md Maniruzzaman; Khan, Md Ismail (Journal of Dhaka Medical College, 2017)
A prescription - a written instruction of doctors to pharmacist to supply drugs in particular form to a patient and the directions to the patients regarding the use of medicines.This study was undertaken to observe the prescribing patterns of the practitioners in Bangladesh, 500 prescriptions were collected randomly from Dhaka city and analyzed using WHO/INRUD indicators. There were average 4.40drugs per prescription.Drugs were prescribed in generic name only in 0.30%. About 48% drugs were prescribed from the essential drug list, only prescriptions were complete. In respect to patient medication information, antibiotics were prescribed in 72% of the prescriptions; injections were prescribed in about 10% of the prescriptions. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 48-51